Schizophrenia in children, adults and older people with intellectual disability compared with the general population: a Swedish register study (IDcare) - Trine Lise Bakken; Anna Axmon; Magnus Sandberg (General Psychiatry)
Background The knowledge about the prevalence of schizophrenia among people with intellectual disabilities (ID) is sparse, particularly concerning the distribution in different age groups.Aims To investigate the prevalence of diagnoses in the schizophrenia spectrum among people with ID compared with the general population (gPop).Methods This was an 8-year longitudinal register study. The participants were all residents of Skåne on 1 January 2014. People with a diagnosis of ID (F7 in International Statistical Classification of Diseases and Related Health Problems 10th Revision) or Down syndrome (DS; Q90), or service and support for people with ID/autism spectrum disorder (ASD) comprised the ID cohort (n=14 716). After excluding family members of people in the ID cohort, the remaining population of Skåne comprised the gPop cohort (n=1 226 955).The primary outcome measure was having at least one diagnosis in the schizophrenia spectrum (F20-F29). Secondary outcomes were single diagnoses within the schizophrenia spectrum.Results The prevalence of schizophrenia spectrum diagnoses was 7.2% in the ID cohort. This was more than an eightfold increase compared with the gPop (relative risk (RR) 8.45; 95% CI 7.94 to 9.00). The risk was also high among children (aged 0–18 years at the start of the study period; RR 9.42; 95% CI 7.36 to 12.05). In the subcohort comprising those with a diagnosis of DS, the risk of schizophrenia diagnosis was more than twice as high as in gPop. Concomitant ASD or genetic syndrome did not carry an excess risk among people with ID when compared with the gPop.Conclusions The findings of the present study support earlier assumptions that people with vulnerable brains develop psychotic disorders more frequently and that the onset age is lower than among people in the gPop. Habilitation services for children and adolescents, as well as general mental health services, should keep in mind that schizophrenia may be present when children and adolescents show severely decreased functioning, anxiety or aggressive behaviour.